The process of teaching‐learning the especific judo technique from the error perspective is the key: O Soto Gari vs. O Soto Guruma - A. Gutiérrez; I. Prieto (Asociación Española de Ciencias del Deporte, 2010)
The present study must know the most frequent errors of the O Soto Gari and O Soto Guruma judo techniques, and clarify the existing differences between both projections in order to improve their process of education. An analysis using video-graphics is applied. It is used as observation and recording method for the mentioned judo techniques being exercised. The analysis is carried out by students of the University of Vigo. They attended the course "Sports of Adversary with Recreational Aims" during approximately four months. The results, presented by statistical means using the software package SPSS 12.0.1, show: 1) O Soto Gari is a technique where the studied judokas reach a greater frequency and diversity of errors than in O Soto Guruma. This allows announcing that for the teaching-learning process later one, due to its greater technical simplicity, should be used before O Soto Gari in. 2) Against the logic expectations, the errors that can be found when practicing the two projections are not as many. Therefore it can be concluded: a) There are not many frequent or routine errors on both projections and b) Errors made don't correspond to the most routine errors found in each technique. Key words:judo, technique, error, initiation, O Soto Gari, O Soto Guruma.